Hubungan Religious Coping dengan Resiliensi pada Pasien Stroke di Wilayah Kerja Puskesmas Purwokerto Selatan - Muhammad Ghazy Setyaputra; Septian Mixrova Sebayang; Ema Wahyu Ningrum (Jurnal Sehat Mandiri, 2023)
Stroke is a disease condition caused by a sudden cessation of blood flow to the brain, either due to blockage or rupture of blood vessels and is the third most common non-communicable disease after hypertension and diabetes. Stroke has a psychological impact that causes the patient to be irresistible. Resilience affects the recovery process in stroke patients. Stroke sufferers who are not resilient are influenced by religious coping (spirituality) where spiritual strength and belief can increase resilience in individuals. The purpose of this study was to determine the relationship between religious coping and resilience in stroke patients in the Work Area of the South Purwokerto Public Health Center. Research design is correlation study survey with a cross sectional time approach. The sample of this research was 45 respondents using simple random sampling technique. Data analysis was determined by the spearman-rank test. The results showed that religious coping in stroke patients in the Work Area of the South Purwokerto Health Center was mostly positive (84.4%). The resilience of stroke patients in the Work Area of the South Purwokerto Health Center is mostly high (86.7%). The results of the Spearman rank correlation test showed that the p-value was 0.0001 (p-value < 0,05). The conclusion is that there is a correlation between Religious coping and Resilience in Stroke patients in work area at South Purwokerto Health Center.